Peningkatan Status Akreditasi 'Unggul' untuk Program Studi Bahasa: Analisis Dokumen Kinerja Program Studi (DKPS) - Hula, Ibnu Rawandhy N.; Mariana, Ana (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2024)
Accreditation is a form of external quality assurance for higher education study programmes to the community and a reference for improving the level.  The main objective of the research is to analyse the study programme performance document (DKPS) to evaluate the readiness of the language study programme in achieving superior accreditation status. This research method uses a mixed method type. Data were collected through the Study Programme Performance Document (DKPS), and Book 4 of LAMDIK. The population of quantitative data totalled 89 items. While the sample consisted of 27 items, purposive sampling focused on standards 5 to 9. This study concluded that based on quantitative data and the contents of the study programme performance document (DKPS) in the form of 6 DTPS, 120 Active Students, and the number of graduates each year (6/10/15/10/20), an average score of 4 and an initial value of 194.80 were obtained. To achieve a superior score (NA ≥ 361), the initial score must still be added with several other scores, such as a) the scores obtained from standards 1 to 4, b) the value of the Self Evaluation Report (LED), c) the value of the field assessment (AL) and practicum, (d) the combined score between two assessors and (e) the final score by the accreditation panel. This research contributes to knowledge on how to improve accreditation scores and grades to be superior along with the formulation of strategies and recommendations to improve accreditation status with four quality dimensions (1) leadership and governance performance, (2) inputs, (3) processes and (4) outputs and outcomes.